Association of extent of resection on recurrence-free survival and functional outcome in vestibular schwannoma of the elderly - Wang, Sophie Shih-Yüng; Machetanz, Kathrin; Ebner, Florian; Naros, Georgios; Tatagiba, Marcos (Frontiers in Oncology, 2023)
Background Despite the ongoing debate on the risk–benefit ratio of vestibular schwannoma (VS) treatment options, watchful observation and radiation are usually favored in the elderly (>65 years). If surgery is inevitable, a multimodal approach after deliberate subtotal resection has been described as a valid option. The relationship between the extent of resection (EOR) of surgical and functional outcomes and recurrence-free survival (RFS) remains unclear. This present study aims to evaluate the functional outcome and RFS of the elderly in relation to the EOR. Methods This matched cohort study analyzed all consecutive elderly VS patients treated at a tertiary referral center since 2005. A separate cohort (<65 years) served as a matched control group (young). Clinical status was assessed by the Charlson Comorbidity Index (CCI), the Karnofsky Performance (KPS), and the Gardner and Robertson (GR) and House & Brackmann (H&B) scales. RFS was evaluated by Kaplan–Meier analysis using contrast-enhanced magnetic resonance imaging to identify tumor recurrence. Results Among 2,191 patients, 296 (14%) patients were classified as elderly, of whom 133 (41%) were treated surgically. The elderly were characterized by a higher preoperative morbidity and worse gait uncertainty. Postoperative mortality (0.8% and 1%), morbidity (13% and 14%), and the functional outcome (G&R, H&B, and KPS) did not differ between the elderly and the young. There was a significant benefit in regard to the preoperative imbalance. Gross total resection (GTR) was accomplished in 74% of all cases. Lower grades of the EOR (subtotal and decompressive surgery) raised the incidence of recurrence significantly. Mean time to recurrence in the surgELDERLY was 67.33 ± 42.02 months and 63.2 ± 70.98 months in the surgCONTROL. Conclusions Surgical VS treatment aiming for complete tumor resection is feasible and safe, even in advanced age. A higher EOR is not associated with cranial nerve deterioration in the elderly compared to the young. In contrast, the EOR determines RFS and the incidence of recurrence/progression in both study cohorts. If surgery is indicated in the elderly, GTR can be intended safely, and if only subtotal resection is achieved, further adjuvant therapy, e.g., radiotherapy, should be discussed in the elderly, as the incidence of recurrence is not significantly lower compared to the young.